Engaging with Policy, Practice and Publics - Hall, Sarah H.; Hiteva, Ralitsa (Policy Press, 2020)
Available Open Access under CC-BY-NC licence. Engagement with non-academic groups and actors - such as policy-makers, industry, charities and activist groups, communities, and the public - in the co-production of knowledge and real-world impact is increasingly important in academic research. Drawing on empirical research, interdisciplinary methodologies, and broad international perspectives, this collection offers a critical examination of the liminal space of interactions between policy and research as spaces of difference and engagement, showing them to be far from apolitical.